Characteristics and Ethnic Distribution of Aortic Aneurysms in a Caribbean Cohort - Ramdass, Michael J.; Persad, Shivani T.; Harnarayan, Patrick (The Thoracic and Cardiovascular Surgeon, 2023)
Background There is a paucity of data regarding relationships between patient demographics and aneurysm characteristics in the West Indies. With this in mind, a retrospective cross-sectional review was conducted analyzing the computed tomography aortogram reports/images of 273 aortic aneurysms.Methods Data were collected and analyzed on ethnicity, size, type, morphology, presence and maximum size of thrombus and aneurysm location, demographics, and clinical presentation with correlations.Results There were 273 patients with aortic aneurysms giving an incidence rate of 4.33 per 100,000 people per annum. Statistically significant associations were noted with age, gender, and ethnicity. All false aneurysms were male (p = 0.004). The average size of aortic aneurysms being 0.7 cm larger in males than females (p < 0.001). Females were more likely to present with rupture (p = 0.001). Thrombus was more likely in males, Black and mixed races, and in the 8th decade (p < 0.001). Mean age of presentation was the highest in East Indians at 78 than the other ethnicities (Chinese: 65, Black: 70, mixed: 71, White: 73).Conclusion Aortic aneurysmal disease is increasing in Trinidad and the Caribbean. Infrarenal fusiform aneurysms are the most common types with many significant differences based on age, gender, and ethnicity in the Caribbean population.
Keywords: aorta/aortic; aneurysm; vascular science